2018
DOI: 10.1186/s13059-018-1480-7
|View full text |Cite
|
Sign up to set email alerts
|

Selection-driven cost-efficiency optimization of transcripts modulates gene evolutionary rate in bacteria

Abstract: BackgroundMost amino acids are encoded by multiple synonymous codons. However, synonymous codons are not used equally, and this biased codon use varies between different organisms. It has previously been shown that both selection acting to increase codon translational efficiency and selection acting to decrease codon biosynthetic cost contribute to differences in codon bias. However, it is unknown how these two factors interact or how they affect molecular sequence evolution.ResultsThrough analysis of 1320 bac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Past reports on the molecular optimization of genetic sequences have shown that transcribed regions of genes can have fine-tuned nucleotide compositions that reduce their biosynthetic cost 20 . For example, DNA coding sequences are found to reduce nitrogen atoms per codon when nitrogen is scarce in the environment 41 , and a large proportion of bacterial genomes present a dual optimization strategy to reduce per-codon nitrogen demand while increasing translation efficiency 42 . Extending these findings, we show that type Ia pmoCAB coding sequences possess an adaptation that minimizes not only nitrogen but also carbon and hydrogen per transcribed codon, while reducing the metabolic burden of erroneous biosynthesis 25 through optimal translation efficiency and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Past reports on the molecular optimization of genetic sequences have shown that transcribed regions of genes can have fine-tuned nucleotide compositions that reduce their biosynthetic cost 20 . For example, DNA coding sequences are found to reduce nitrogen atoms per codon when nitrogen is scarce in the environment 41 , and a large proportion of bacterial genomes present a dual optimization strategy to reduce per-codon nitrogen demand while increasing translation efficiency 42 . Extending these findings, we show that type Ia pmoCAB coding sequences possess an adaptation that minimizes not only nitrogen but also carbon and hydrogen per transcribed codon, while reducing the metabolic burden of erroneous biosynthesis 25 through optimal translation efficiency and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to translation, codon usage bias has been associated with transcriptional selection 15 and optimization of transcription efficiency 16 . Recent reports support the idea that codon variants also define the energy and cellular resources required for transcript biosynthesis [17][18][19][20] . However, in contrast to translation, the potential links between position-dependent codon usage bias at the 5 -end of CDSs and transcription optimization have yet to be investigated.…”
mentioning
confidence: 83%
“…The commands used to compile the ORFeomes were "Latest RefSeq" and "Exclude anomalous". A smaller representative dataset of Bacteria ORFeomes was compiled based on a previously curated list that has even representation across phyla 18 . The Archaea and Fungi ORFeomes were relatively small so all were included in all analyses.…”
Section: Sequence and Genomic Analysesmentioning
confidence: 99%
“…Orange3 data mining software (35). Next, we calculated the selection on transcript translational efficiency (St) and selection on transcript biosynthetic cost (Sc), as described by Seward & Kelly (36,37). Subsequently, we performed the Akashi Test (38) to calculate the selection on translation accuracy using the software Seforta (39).…”
Section: Characterisation Of Codon Usagementioning
confidence: 99%
“…We selected codon usage metrics that are calculated individually for each gene. For each CDS, we calculated various codon usage metrics (Table S1) by using EMBOSS (40), CodonW (41), CAIcal (42), coRdon (43), stAIcalc (44), and scripts included in the original manuscripts, such as CodonMuSe (37) and iCUB (45). For codon usage metrics that require highly expressed genes as a reference, we employed the CDSs of the top 10% proteins with the highest overall median abundance.…”
Section: Feature Compilation For Machine Learningmentioning
confidence: 99%